Determinants analysis on job performance of workers in plantation sectors / Mohammad Syazrul Syahril Hassan - Hassan, Mohammad Syazrul Syahril (Faculty of Plantation and Agrotechnology, 2018)
Currently, Human Resource Management is becoming crucial because employees and their skills are the most important aspect that affecting productivity of the organization. Motivation is one of the most important tools that encourage employees to perform as well as to attract and retain potential candidates. The main purpose of this study is to investigate the determinants analysis on job performance of workers in plantation sectors at Merlimau, Melaka. A qualitative case study methodology was used by using questionnaires. The questionnaires were distributed to the sample of 59 respondents in order to determine the factors that lead to job performance that is training, benefits, and working environment. From this study, we able to measure the relationship between independent variables and the dependent variable and also can suggest recommendation to the management in order to promote and improve job performance. Correlation analysis is used to analyse the collected data. The result of correlation analysis show that the relationship between explanatory variables and dependent variables affecting the job performance of plantation workers. All motivation factors is required in improving job performance, with improve the motivation factors that will lead to employee satisfied, it will further encourage better performance. Employees spend large portion of their time in the workplace. Therefore, organizations have to create happy and better organizational culture where employees enjoy their time and like to spend as much as they can in the workplace. This practice can increase the employee retention and loyalty to the organization and reduce their absenteeism.